Pengaruh Penggunaan Substitusi Tepung Labu Kuning(Cucurbhitamoschata) Pada Pembuatan Roti Tawar Ditinjau DariTingkat Pengembangan Dan Daya Terima - Nurmadiani, Effa, Pramudya Kurnia, STP, M.agr, Eni Purwani, SSi., MSi (2015)
Background:Pumpkin is a food that has the potential to be developed into flour, as an alternative that reduce the consumption of wheat flour increases in recent 3 years (2012-2014).To substitution pumpkin flour baking test white be done as food diversification efforts. Objective: Todetermine the effect of the use of pumpkin flour substitution on the level of development and acceptance of bread Methods: The studyexperiment with data analysis using one way ANOVA and LSD (Lest Significal Different).The study design used completely randomized design with threetreatmentscomparison flour and pumpkin. Results:This study showed that bread substituted pumpkin 0% and 15% showed high levels of development and the most preferred white breadpanelistis substituted pumpkin flour by 15% Conclusion:There is a pumpkin flour substitution effect on the level of development of white bread.Bread substituted pumpkin 0% and 15%showed high development of the highest. There is a substitution effect flour pumpkin against acceptance of color, aroma, flavor, texture and overall of pumpkin bread.The most preferred white bread panelist is substituted pumpkin flour by 15%